Cultural heritage: from Italy smart conservation and protection from fire, bacteria, water - Camilla Ghedini (Archeomatica)
Makros founded in 2018, is based in Ferrara, Emilia Romagna. its organization includes a technical scientific committee of biologists, mathematicians, physicists, computer technicians and scientists, architects, who direct research and development, to which about half of the profits are allocated. Makros owns six patents, which can be combined together. Clients are public, private and even religious authorities and institutions.